2019
DOI: 10.1172/jci.insight.131092
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional heterogeneity of fibroblasts is a hallmark of the aging heart

Abstract: Single-nucleus RNA-sequencing reveals cellular heterogeneity of cardiac cells in aging. To comprehensively decipher the expected cellular responses to intrinsic cardiac aging, we applied microdroplet-based single-nucleus RNA-sequencing (9) of cross-sections of snap-frozen heart samples from 3 syngeneic young male mice (12 weeks old) and 3 aged male mice (18 months old). In total, we analyzed 14,827 nuclei from young hearts and 12,981 nuclei from old hearts (Supplemental Table 1; supplemental material available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(136 citation statements)
references
References 41 publications
6
130
0
Order By: Relevance
“…In addition to functional diversity found in normal development, transcriptional heterogeneity can arise from pathological or compensatory processes associated with aging [31][32][33] . Skeletal muscle undergoes dramatic age-related changes with respect to functional deterioration and regenerative decline [34][35][36][37] , and so we next asked if the aging process impacted myonuclear transcription.…”
Section: Mainmentioning
confidence: 99%
“…In addition to functional diversity found in normal development, transcriptional heterogeneity can arise from pathological or compensatory processes associated with aging [31][32][33] . Skeletal muscle undergoes dramatic age-related changes with respect to functional deterioration and regenerative decline [34][35][36][37] , and so we next asked if the aging process impacted myonuclear transcription.…”
Section: Mainmentioning
confidence: 99%
“…Interestingly, this FB subset was shown to be reduced after MI [7]. While these examples highlight the interaction of FBs with CM, bioinformatics analysis of single cell sequencing data sets suggest that the main interacting cell type of fibroblasts in the heart may be endothelial cells, which may trigger further research to elucidate the interactions between these two cell types [7,89].…”
Section: Fibroblastsmentioning
confidence: 99%
“…Single nucleus sequencing revealed that cardiac FBs of the aging heart highly express the SASP factor PAI-1. PAI-1 was further identified as one of the crucial factors in conditioned medium from age-heart derived FB, which interferes with endothelial cell angiogenesis [89]. In addition, mesenchymal stromal cells display senescence and SASP in the aging heart, which contributes to the recruitment of CCR-2-dependent monocytes.…”
Section: Senescent Cells and Sasp In The Aging Heartmentioning
confidence: 99%
“…Intact adult CMs are too large to apply to a droplet system, and thus some researchers have extracted CM nuclei for use with this system to perform high-throughput scRNA-seq. Single-nucleus RNA-seq (snRNA-seq) of tens of thousands of nuclei extracted from healthy mice and from a murine MI model were performed using Chromium [23,24]. The results revealed that dedifferentiation may be an important prerequisite for CM proliferation and demonstrated the limited but measurable cardiac myogenesis after MI.…”
Section: Murine Adult Heartmentioning
confidence: 99%
“…In the heart, ligand-receptor analysis revealed interactions between cardiac cell types in homeostasis and injury [23,27]. In particular, there is a strong association between fibroblasts and endothelial cells after injury or during aging.…”
Section: Cell-cell Interactionsmentioning
confidence: 99%